The nugget - Deutermann, P. T., (Peter T.), 1941- (St. Martin's Press, 2019)
Lieutenant Bobby Steele, USN, is a fresh-faced and eager naval aviator: a "Nugget," who needs to learn the ropes and complex procedures of taking off and returning safely to his aircraft carrier. A blurry night of drinking lands him in an unfamiliar bed aboard the USS Oklahoma; later that day, the Japanese destroy Pearl Harbor. After cheating death and losing his friend in this act of war, the formerly naive Steele vows to avenge the attack. Flying sea battle after battle, Steele survives the most dangerous air combat in World War II, including Midway, is shot down twice, rescued twice, and eventually leads a daring mission to free prisoners from a secluded Japanese POW camp. Packed with authentic military action on land and at sea in the Pacific Theatre of WWII and featuring a memorable protagonist based on a true-life hero, The Nugget is a first-class adventure by a former commander whose family served in the Pacific.